The Implicit Association of High-Fat Food and Shame Among Women Recovered From Eating Disorders - Elran-Barak, Roni; Dror, Tzipi; Goldschmidt, Andrea B.; Teachman, Bethany A. (Frontiers in Psychology, 2020)
Background Despite the growing literature about recovery from eating disorders (EDs), it is still unknown if women who report being recovered from EDs present with differing implicit attitudes about high-fat (vs. low-fat) food relative to women who report having a current ED and women who report never having had an ED. Methods Female volunteers (N = 2,785) to the Project Implicit Mental Health (PIMH) website (https://implicit.harvard.edu/) were divided into three ED groups: current ED (n = 335), prior ED (n = 393), and healthy controls (n = 1,843). Participants completed, between 2016 and 2017, a background questionnaire, together with the Implicit Association Test (IAT), measuring implicit associations between high-fat (vs. low-fat) food and shame (vs. acceptableness). Linear regression models were conducted to examine cross-sectional differences between groups. Results Women with prior EDs had stronger implicit associations relative to healthy controls (p = 0.041) and similar implicit associations relative to women with current EDs (p = 0.424). Discussion The implicit association between high-fat food and shame may not diminish over time among women with EDs. Future longitudinal studies are warranted to clarify whether an experience of EDs may leave a “scar,” manifested in specific implicit associations, that may potentially lead to recurrence after remission.